Nanohelix‐Induced Optical Activity of Liquid Metal Nanoparticles. Issue 17 (23rd March 2022) - Yang, Lin; Ma, Yicong; Lin, Chao; Qu, Geping; Bai, Xiaopeng; Huang, Zhifeng
Abstract: Liquid metals (such as gallium or Ga) exist in liquid states under ambient conditions and are hardly sculpted in chiral structures. Herein, through electron‐beam evaporation of Ga, hemispherical achiral Ga nanoparticles (NPs) are randomly immobilized along helical surfaces of SiO2 nanohelices (NHs), functioning as a chiral template. Helical assembly of Ga NPs shows chiroplasmonic optical activity owing to collective plasmon–plasmon interactions, which can be tuned as a function of a helical SiO2 pitch ( P ) and the amount of Ga evaporated. At a P of ≈150 nm, the chiroplasmonic optical activity, evaluated with anisotropic g ‐factor, can be as large as ≈0.1. Because the SiO2 NHs and Ga NPs have high environmental stability of nanostructures, the chiroplasmonic optical activity shows excellent anti‐aging stability, despite slight blue shift and chiroplasmonic degradation for the first 2 weeks. Spontaneous oxidation of the Ga NPs enables the formation of dense Ga2 O3 layers covering Ga cores to prevent further oxidation and thus to stabilize the chiroplasmonic optical activity. This work devises an alternative approach to impose optical activity onto Ga NPs, providing an additional degree of freedom (i.e., chirality) for Ga‐based flexible electronic devices to develop advanced applications of 3D display, circular polarizers, bio‐imaging, and bio‐detection. Abstract : An assembly of achiral gallium (Ga) nanoparticles (NPs) along helical surfaces of SiO2 nanohelices imposes chiroplasmonic optical activity onto Ga NPs. The chiroplasmonic optical activity, evaluated with anisotropic g ‐factors, can be tuned as large as ≈0.1, and shows excellent anti‐aging stability under ambient conditions owing to self‐termination of spontaneous oxidation of the Ga NPs.